2009
DOI: 10.2190/pm.39.2.g
|View full text |Cite
|
Sign up to set email alerts
|

Religious Involvement and Cigarette Smoking among Iranian University Students

Abstract: Religious activities may have a protective role against cigarette smoking among Muslim college students in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In a study by Atkin et al interviewing 1330 randomly selected teenagers, among the various factors entering a logistic regression model, religious attendance or participation and positive peer role modeling showed the strongest inhibitive effects on smoking [58]. A study of 833 university students revealed that more frequent religious involvement was associated with a smaller likelihood of cigarette smoking (OR = 0.53, p < 0.01) along with high exam scores, even after controlling for baseline variables [55].…”
Section: Adolescents and Young Adultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study by Atkin et al interviewing 1330 randomly selected teenagers, among the various factors entering a logistic regression model, religious attendance or participation and positive peer role modeling showed the strongest inhibitive effects on smoking [58]. A study of 833 university students revealed that more frequent religious involvement was associated with a smaller likelihood of cigarette smoking (OR = 0.53, p < 0.01) along with high exam scores, even after controlling for baseline variables [55].…”
Section: Adolescents and Young Adultsmentioning
confidence: 98%
“…A number of studies on the relationship between religion and cigarette smoking portray a strong correlation, yet the majority of them are cross-sectional [35,[55][56][57][58].…”
Section: Adolescents and Young Adultsmentioning
confidence: 99%
“…In addition, some studies reported that Muslims who were minorities in the countries in which they lived, also had higher rates of smoking (Islam and Johnson, 2005;Nierkens, Stronks, van Oel, de Vries, 2005). Nakhaee et al (Nakhaee, Divsalar, and Jadidi, 2009) concluded that religious activities may have a protective role against cigarette smoking among Muslim university students (Nakhaee et al, 2009). We aimed to evaluate the adverse effects and results of smoking cessation treatment during Ramadan.…”
Section: Discussionmentioning
confidence: 95%
“…Cigarette smoking and alcohol consumptions are two known risk factors for gastrointestinal (GI) cancers, especially upper GI. Fortunately, these are less frequent in Iran as a result of religious followings 8 , 9 . Cautionary smoking habits with consequent oral cancers are increased among women.…”
Section: Elderly Oral Health Complicationsmentioning
confidence: 99%